(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The four essential factors in Forensic Anthropology, representing in determining personal identification are age, sex, stature and ethnicity. Among this ‘big fours’ of the biological profile, determination of stature is considered as one of the main parameter of personal identification in forensic examinations. Thus, this study will aim to correlate relation between hand and foot measurements with stature of individual. Aim of the study: The study aimed to estimate the relationship between statures of an individual on the basis of hand and foot prints, in Indian populations. Materials and Method: The study group comprised of 100 subjects (age group above 18 years) with normal growth and development. Measurement of height: The measurements of height was made using standard anthropometer by making the subject stand erect on the horizontal plane. The distance of the subject from the ground to the highest point of the vertex in the median sagittal plane was recorded. • a) Hand length and Hand breadth: Hand length (HL) was measured from mid-point below radial and ulnar tuberosity to tip of middle finger. Hand breadth (HB) was measured from base of 5th to 2nd metacarpus by drawing the outline of hand on paper. • b) Foot length and breadth: The foot length was measured as a direct distance from the most posterior point of back to tip of the Hallux or to tip of the second toe .The foot breadth was measured as the direct distance between the most prominent point on medial side and the most prominent on lateral side. • d) Heel Ball Index Measurement The breadth of the foot at ball and at heel (BBAL, BHEL) were measured. The HB Index of the foot was calculated as (BHEL+ BBAL) x 100. Results: Correlation of the various hand and foot parameters showed a regression coefficient range of 0.331-0.377. Among all variables measured, hand length exhibited the highest correlation with stature (r value of 0.377 p-value < 0.003). Further forward stepwise linear regression analysis [Height = 115.426+2.615* Hand length (Left)] established hand length to be the single best predictor of height (r value of 0.377 and standard error of 7.35cms). Conclusion: Thus, the foot length provides highest reliability and accuracy in estimating stature of unknown males and females. Also this study will help to generate population-specific equations using a simple linear regression statistical method.